A practicum at SYSU Intenational, Inc. Novaliches, Quezon City, Metro Manila - Molejon, Vincenzo A. (2010)
The 288-hour plant practice was spent at SYSU International, Inc. Novaliches, Quezon City, Metro Manila. During the plant practice the author was assigned at the Quality Control and Quality Assurance department. The author was given the chance to conduct different chemical and physical analysis such as determining yhe %salt, %acidity, viscocity, refractive index, filling and cooling temperatures and pH. The author was also assigned to assist the sensory evaluation section-conducting organoleptic tests to determine the aesthetic stability of products. In addition, the author was able to assist in the microbiology laboratory doing media preparation, incubation of cultures and microscopy. On the non-lab aspect, the author was assigned to check the quality of the pouches for the products conducting physical evaluation such as smearing, vanishing effects, color contrast, doctor marks, pouch declaration and pouch codes. During the plant practice, the author was able to apply his knowledge in food technology both in the management and science disciplines. The author was able to understand how science and management are intertwined in the business and how they function mutually in order to produce wholesome, safe and good quality products. Further, the author was able to evaluate the processing section and the production side in general. Based on the authors' exposure in the plant, he was able to formulate recommendations for the benefit of the company